Acute Frontal Lobe Dysfunction Following Prefrontal Low-Frequency Repetitive Transcranial Magnetic Stimulation in a Patient with Treatment-Resistant Depression - Carle, Guilhem; Touat, Mehdi; Bruno, Nicolas; Galanaud, Damien; Peretti, Charles-Siegfried; Valero-Cabré, Antoni; Levy, Richard; Azuar, Carole (Frontiers in Psychiatry, 2017)
The potential of repetitive transcranial stimulation (rTMS) to treat numerous neurological and psychiatric disorders has been thoroughly studied for the last two decades. Here we report for the first time, the case of a 65-year-old woman suffering from treatment-resistant depression who developed an acute frontal lobe syndrome following eight sessions of low frequency rTMS (LF-rTMS) to the right dorsolateral prefrontal cortex whilst also treated with sertraline and mianserin. The pathophysiological mechanisms underlying such an unexpected acute frontal lobe dysfunction are discussed in relation to the therapeutic use of LF-rTMS in combination with pharmacotherapy in depressed patients.